Coenzyme Q10 and its liposomal form prevent copper cardiotoxicity by attenuating oxidative stress, TLR-4/NF-κB signaling and necroptosis in rats: CoQ10 and L-CoQ10 prevent Cu cardiotoxicity in rats - Alghibiwi, Hanan K.; Alhusiani, Ahlam M.; Sarawi, Wedad S.; Fadda, Laila; Alomar, Hatun A.; Alsaab, Juman S.; Hasan, Iman H.; Alonazi, Asma S.; Alrasheed, Nouf M.; Alhabardi, Samiah (Cellular and Molecular Biology, 2025)
Copper (Cu) is an essential element involved in numerous biochemical, metabolic and cellular processes. Excessive exposure to the pesticide copper sulfate (CuSO4) was associated with toxic effects. This study aims to evaluate the efficacy of Coenzyme Q10 (CoQ10) and its liposomal form (L-CoQ10) against myocardial injury induced by CuSO4, pinpointing the involvement of redox imbalance, TLR-4/NF-κB signaling and apoptosis. Cardiac injury in rats was induced by daily oral doses of CuSO4 for 7 days, the rats were treated orally with either CoQ10 or L-CoQ10 concurrently with CuSO4 for 7 days. Elevated serum cTnI, CK-MB and LDH were observed in CuSO4-intoxicated animals. Additionally, cellular antioxidant biomarkers were decreased and the expression levels of cardiac MDA, TLR-4, NF-κB, IL-6, IL-1β, and TNF-α were upregulated. CoQ10 and L-CoQ10 prevented myocardial injury and decreased the levels of both MDA and pro-inflammatory cytokines. CoQ10 and L-CoQ10 enhanced antioxidant capacity and Bcl-2, and downregulated caspase-3, Bax, p53, RIP3, MLKL, caspase-8 and TLR-4/NF-κB signaling. In conclusion, CoQ10 and L-CoQ10 effectively prevent CuSO4 cardiotoxicity in rats. Attenuation of redox imbalance, TLR-4/NF-κB signaling, pro-inflammatory response, and necroptosis along with enhancement of antioxidant response mediated their cardioprotective efficacy. CoQ10 could be valuable in protecting people vulnerable to Cu toxicity.